Design by definition - McGuane, Elizabeth (Book Apart (Series), 2023)
When we think of design primarily in terms of visual representation, we neglect an essential piece of the creative process. The words we use to form concepts can also powerfully shape a design project from start to finish—giving clarity to goals, precision to names and structure, and purpose to stylistic choices. Elizabeth McGuane offers a fresh, empowering framework for design. Drawing from her experience on the forefront of web, mobile, and product design, she shows us how to harness the potency of words and language to uplift and illuminate rather than encumber. Learn how to effectively apply semantic concepts, use language to frame design problems clearly, and integrate elements of style such as metaphor and nomenclature, to strengthen your design process.